Academic monitoring and its contributions to the teaching-learning process in the Nursing course (Research, Society and Development, 2024)
Academic monitoring improves the student-monitor's orality and interpersonal relations, facilitating access to knowledge through language that is closer and more adapted to the reality of the student being monitored. This study aims to report on the experience, importance and contributions of tutoring in the Semiology/Semiotechnics and Adult Intensive Care Unit subjects in the Hospital Nursing Department. This is a descriptive study of the experience report type, describing the activities developed in an academic monitoring during the period 2022.2 and 2023.1, covering the didactic tools used by the monitor and the perceptions about the teaching-learning process of the situations experienced. Methodological tools were used to improve teaching and make learning meaningful, such as: summaries and mind maps on airway aspiration, bed baths, injury assessment and vital signs, handouts on "anamnesis and physical examination" and "wounds and dressings", and the use of online tools for teaching. This monitoring process brings positive results for academic, interpersonal and professional training, making people feel more secure and confident. Therefore, academic mentoring is fundamental for all the members who take part, from the teachers to those being mentored, in order to expand knowledge, safety and professional and interpersonal relationships, and should be a practice encouraged in higher education institutions.